Influence of salinity on germination and early seedling root growth traits of alfalfa (Medicago sativa L.) landraces collected in Southern Algerian oases - Kadri, Adel; Chaabena, Ahmed; Abdelguerfi, Aissa; Laouar, Meriem (Agriculture and Natural Resources, 2022)
The perennial forage Medicago sativa L. (alfalfa) is a very important leguminous forage crop. Screening of alfalfa landraces to salt tolerance through the seed germination and early seedling root growth stages is crucial for their evaluation. Ten local landraces of alfalfa from Algerian oases and one commercial cultivar (Giulia) were evaluated for germination and early seedling root growth under increasing NaCl salt concentrations (0 mM, 85.6 mM, 171.1 mM, 256.7 mM, 342.2 mM). Five traits were studied: precocity of germination (PG), final germination rate (FGR), mean germination time (MGT), radicle length (RL) and the IC50 which represents the osmotic potential that inhibits 50% of viable seeds. The results showed that there were significant differences among alfalfa cultivars under non-stress and salt stress for all the studied traits, suggesting high diversity among the cultivars. Hassi Laabid had the highest FGR (mean ± SD; 74.53 ± 32.88), whereas Megganine had the lowest FGR (63.20 ± 29.07). For MGT, Megganine had the highest value (3.49 ± 0.94) while Hassi Laabid had the lowest value (2.29 ± 1.15). Giulia had the highest reduction while Guemar had the lowest reduction under increasing NaCl salt concentration. The cultivars with the greatest IC50 values were Janet (-0.77 MPa), Hassi Laabid (-0.74 MPa), Temacine (-0.73 MPa) and In Salah (-0.69 MPa), indicating that they required the greatest osmotic potentials to limit their germination and would potentially be more tolerant to the effect of NaCl during germination and seedling establishment. Correlation coefficients between all possible combinations were estimated and the results indicated that PG, FGR, MGT and RL had significant negative or positive correlations with each other.